2005
DOI: 10.1002/hipo.20091
|View full text |Cite
|
Sign up to set email alerts
|

Sparse, environmentally selective expression ofArc RNA in the upper blade of the rodent fascia dentata by brief spatial experience

Abstract: After a spatial behavioral experience, hippocampal CA1 pyramidal cells express the activity-regulated, immediate early gene Arc in an environment-specific manner, and in similar proportions ( 40%) to cells exhibiting electrophysiologically recorded place fields under similar conditions. Theoretical accounts of the function of the fascia dentata suggest that it plays a role in pattern separation during encoding. The hypothesis that the dentate gyrus (DG) uses a sparse, and thus more orthogonal, coding scheme ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

78
306
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(394 citation statements)
references
References 37 publications
78
306
10
Order By: Relevance
“…In that respect, it is interesting that earlier studies have shown distinct strain-specific patterns of MF lamination in mice, which were associated with an altered distribution of MFTs (42) and correlated with performance in cognitive tasks, including some spatial WM tasks (17,18). There is also evidence of differential activation of the SPBs and IPBs of the DG (43), and altered segregation of the SP and IP blades may change the respective connectivities of these blades with CA3. Although the pattern of MF lamination has not been explicitly probed in patients with SCHZ, one study has reported lower numerical density of MFTs in CA3 (44), and another study showed lighter overall staining with an MF specific marker (45) consistent with changes occurring in this pathway.…”
Section: Discussionmentioning
confidence: 90%
“…In that respect, it is interesting that earlier studies have shown distinct strain-specific patterns of MF lamination in mice, which were associated with an altered distribution of MFTs (42) and correlated with performance in cognitive tasks, including some spatial WM tasks (17,18). There is also evidence of differential activation of the SPBs and IPBs of the DG (43), and altered segregation of the SP and IP blades may change the respective connectivities of these blades with CA3. Although the pattern of MF lamination has not been explicitly probed in patients with SCHZ, one study has reported lower numerical density of MFTs in CA3 (44), and another study showed lighter overall staining with an MF specific marker (45) consistent with changes occurring in this pathway.…”
Section: Discussionmentioning
confidence: 90%
“…Multiple theories have hypothesized that the hippocampus serves to reduce interference via a process referred to as pattern separation (Marr 1971;Shapiro and Olton 1994;McClelland et al 1995;Rolls 1996). Given its sparse pattern of activity (Barnes et al 1990;Chawla et al 2005), particular attention has been paid to the DG as a potential mediator of pattern separation (Gilbert et al 2001;Lee et al 2004;Leutgeb et al 2007;Clelland et al 2009). A failure in pattern separation may provide an alternative explanation for the deficits we observe in our ADX rats.…”
mentioning
confidence: 79%
“…Evidence from electrophysiological and immediate-early gene imaging experiments suggests that only a small portion of neurons within a region encodes any one memory (Guzowski et al, 1999;Vazdarjanova et al, 2006;Reijmers et al, 2007). This seems particularly true in the dentate gyrus (DG) layer of the hippocampus, which exhibits strikingly sparse activity patterns during experiences (Chawla et al, 2005;Leutgeb et al, 2007). The DG is important in hippocampal dependent learning, including contextual fear memory (Hernańdez-Rabaza et al, 2008).…”
Section: Introductionmentioning
confidence: 99%